Advancing Criminal Justice Reform through Restorative Justice: A Narrative Review - Abdulovna, Daryna Dzemish (Yayasan Sinergi Kawula Muda, 2024)
This study presents a comprehensive narrative review of restorative justice within criminal justice systems, analyzing its potential as a reformative alternative to retributive practices. The review aims to synthesize empirical findings on the impact of restorative justice on recidivism reduction, victim satisfaction, and systemic transformation. Literature was systematically collected using databases such as Scopus, PubMed, and Google Scholar, employing keywords like